Construction of a novel shuttle vector for use in Haemophilus influenzae and H. parainfluenzae - Robinson, E; Juhas, M; Hood, D; Crook, D (2010)
Haemophilus influenzae is an important human pathogen. A number of complete genome sequences of various haemophili are available; however, functional studies have been limited by the lack of an effective shuttle vector which functions in all strains. Here, we have constructed a shuttle vector, pEJ6, which transfers genes between Escherichia coli and H. influenzae and H. parainfluenzae. The vector contains an origin of replication from pLS88 which is functional in E. coli and H. influenzae. In addition it contains an RP4 mobilisation region. The vector can be introduced by electroporation and conjugation into capsulate and non-typeable H. influenzae and is functional for allelic replacement and mutant complementation. The vector will be useful for investigating gene function in Haemophilus spp. © 2010 Elsevier B.V.